Direct Intra-family Violence Perceived by Adolescents - Marioly Ruíz Hernández; Mario Alzuri Falcato; Laura Magda López Angulo; Yoan Hernández Cabrera; Yanara Calzada Urquiola (Revista Finlay)
Foundation: it is estimated that each year around 133-275 million adolescents are exposed to domestic violence in the world. This situation is a cause of concern for world public health. Objective: to determine the perception which adolescents have of direct family violence. Methods: a descriptive cross-sectional study was conducted at the Frank País junior high school in the municipality of Cienfuegos in the years 2015-2016. The universe included 218 adolescents who attended the eighth grade, all of the students of 4 from the 6 groups of the school year were chosen. The sample consisted of 145 students who were applied questionnaire made for this purpose, a quantitative analysis of the data obtained was carried out. The variables studied were: perception of family violence according to their typologies, sex, types of families according to number of members and ontogenesis, perpetrator and perception of family functioning. Statistical software SPSS version 15.0 and descriptive statistics procedures were used. Results: it was demonstrated that seven out of ten adolescents perceive direct family violence, the psychological one was the most usual, followed by negligence and abandonment and then physical, the level of very frequent and frequent in its presentation shows great significance. The perception of violence for both sexes was similar in figures for psychological and physical violence, was higher in adolescents living in single-parent homes with the mother, in large, extended and dysfunctional families. Conclusions: it is confirmed that the adolescents included in the study have a high perception of direct intra-family violence.